Limits of detection in chemical analysis - Voigtman, Edward, 1949- (Chemical analysis ;, 2017)
Details methods for computing valid limits of detection.-Clearly explains analytical detection limit theory, thereby mitigating incorrect detection limit concepts, methodologies and results -Extensive use of computer simulations that are freely available to readers -Curated short-list of important references for limits of detection -Videos, screencasts, and animations are provided at an associated website, to enhance understanding -Illustrated, with many detailed examples and cogent explanations.